2013
DOI: 10.1007/s10853-013-7447-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nanosized magnesium ferrite powders by a starch-gel process and corresponding ceramics

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 55 publications
3
27
0
2
Order By: Relevance
“…[30] The bandgap energy E g was determined by finding the intercept of the straight line in the low-energy rise of the plot of [F(R 1 ) hn] 1/2 for the indirect allowed transition versus hn,w here hn is the incident photon energy.F or MgFe 2 O 4 ,t he bandgap is in the range 1.7-1.9 eV,w hich is about 0.2 eV lower than the literature values. [30] The bandgap energy E g was determined by finding the intercept of the straight line in the low-energy rise of the plot of [F(R 1 ) hn] 1/2 for the indirect allowed transition versus hn,w here hn is the incident photon energy.F or MgFe 2 O 4 ,t he bandgap is in the range 1.7-1.9 eV,w hich is about 0.2 eV lower than the literature values.…”
Section: Resultsmentioning
confidence: 99%
“…[30] The bandgap energy E g was determined by finding the intercept of the straight line in the low-energy rise of the plot of [F(R 1 ) hn] 1/2 for the indirect allowed transition versus hn,w here hn is the incident photon energy.F or MgFe 2 O 4 ,t he bandgap is in the range 1.7-1.9 eV,w hich is about 0.2 eV lower than the literature values. [30] The bandgap energy E g was determined by finding the intercept of the straight line in the low-energy rise of the plot of [F(R 1 ) hn] 1/2 for the indirect allowed transition versus hn,w here hn is the incident photon energy.F or MgFe 2 O 4 ,t he bandgap is in the range 1.7-1.9 eV,w hich is about 0.2 eV lower than the literature values.…”
Section: Resultsmentioning
confidence: 99%
“…For the case of ferrite nanoparticles, up to this moment, only copper, cobalt, nickel, zinc and several mixed-metal and core-shell ferrites are being applied in the catalytic reactions, mainly processes of the synthesis and destruction of organic compounds. Methods for their preparation are described elsewhere (Kasi Viswanath, Murthy, 2013;Pinheiro Bragam et al, 2011;Koferstein, 2013;Gatelite et al, 2011). The synthesis conditions have strongly influenced on the crystal structure, crystallite size, microstructure, magnetic and photocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various ferrite compounds, magnesium ferrite (MgFe 2 O 4 ) nanoparticles is one of the most important functional soft magnetic materials. It has excellent chemical stability with inverse spinel structured, which have found a number of modern technological applications in microwave devices, catalysis, adsorption, gas and humidity sensor, ferrofluid technology, fuel cells, magnetic core of coils and also used in an inorganic pigment [11][12][13]. Aono et al [14] found that MgFe 2 O 4 has the highest heating ability compare to other commercial ferrite powders of MFe 2 O 4 (M = Mg, Mn, Fe, Co, Ni, Cu and Sr) in alternating magnetic field which is one of the interesting applications in hyperthermia therapy.…”
Section: Introductionmentioning
confidence: 99%